THE EXTRACT OF CHLORELLA VULGARIS PROTECTS TRANSFORMED RETINAL GANGLION CELLS FROM OXIDATIVE STRESS-INDUCED CELLS DEATH - Kim, Kyung-A; Cha, Kwang Hyun; Choi, Soon-Jung; Pan, Cheol-Ho; Jung, Sang Hoon (WILEY-BLACKWELL, 2014)
This study investigated whether an extract of Chlorella vulgaris (ECV) could ameliorate the negative influence of N-methyl-d-aspartate (NMDA) on the retinas of rats and decrease oxidative stress-induced cell death in transformed retinal ganglion cells (RGC-5). The ECV was shown to attenuate the negative effect of l-buthionine-(S,R)-sulfoximine (BSO) and glutamate on RGC-5 cells. ECV also decreased the expression of apoptotic proteins induced by BSO and glutamate. NMDA affected the thickness of the retinal inner plexiform layer (IPL) and increased the number of TUNEL-positive RGCs. However, ECV treatment was protective against IPL thinning and reduced the number of TUNEL-positive cells in the ganglion cell layer. Our results clearly demonstrate the neuroprotective effect of ECV on retinal degeneration both in vitro and in vivo. Practical ApplicationsChlorella vulgaris is used in alternative medicine and traditional foods because of its high nutritional content and significant amounts of lutein, which may be beneficial in protecting against age-related eye diseases such as cataract, age-related macular degeneration (AMD), and glaucoma. However, its protective effect against glaucoma-related retinal ganglion cell degeneration has not been investigated. This study aimed to examine whether the extract of C.vulgaris (ECV) could be protective against retinal degeneration. Our results indicate that ECV can protect retinal cells from oxidative stress-induced damage both in vitro and in vivo. These effects may be due to the anti-apoptotic potencies of compounds contained in C.vulgaris. Thus, C.vulgaris may be a useful supplement to prevent retinal degeneration.
Keywords: DIFFERENTIATED RGC-5 CELLS; WATER EXTRACT; IN-VITRO; LUTEIN; CAROTENOIDS; ANTIOXIDANT; GLUTAMATE; GLAUCOMA; DAMAGE; PROLIFERATION